SARS-CoV-2 in Kidney Transplant Patients: A Real-Life Experience - Pinchera, Biagio; Spirito, Lorenzo; Ferreri, Lucia; Rocca, Roberto La; Celentano, Giuseppe; Buonomo, Antonio Riccardo; Foggia, Maria; Scotto, Riccardo; Federico, Stefano; Gentile, Ivan; Carrano, Rosa, “Federico II” COVID-19 Team; et al. (Frontiers in Medicine, 2022)
Background The COVID-19 pandemic has significantly impacted on the management of solid organ transplant recipients and on clinical evolution in post-transplantation. Little is known on the impact of SARS-CoV-2 infection in these patients. The severity and lethality of this disease in solid organ transplant patients are higher than general population. This study aims to describe clinical characteristics of SARS-CoV-2 infection in solid organ transplant recipients followed in our center. Methods In this observational study, we enrolled kidney transplant patients attending the A.O.U. Federico II of Naples from March 2020 to January 2021. For each patient we evaluated the epidemiological and clinical characteristics as well as outcome. Results We enrolled 369 kidney transplant patients (229, male, 62%). Of these, 51 (13.8%) acquired SARS-CoV-2 infection and 29 showed symptomatic disease. Of the 51 patients with the infection, 48 (94.11%) had at least one comorbidity and such comorbidities did not constitute a risk factor for a more severe disease. Hospitalization was necessary for 7 (14.7%) patients. Of these, 2 required low-flow oxygen supplementation, 3 non-invasive/high flow ventilation and 2 invasive ventilation. Finally, 2 patients died. Conclusions Our study shows a lower mortality and hospitalization rate compared to figures available in the literature (4% vs 13-30% and 14% vs 32-100%, respectively). Furthermore, the comorbidities examined (hypertension, dyslipidemia, and diabetes) did not constitute a risk factor for a more severe disease condition in this patient category. Further studies with larger sample size are necessary to confirm these data.